THE ECONOMIC EFFECTS OF FARM VEHICLE-RELATED TRAFFIC ACCIDENTS – A COMPARATIVE ANALYSIS OF WESTERN AND NORTHERN SERBIAN MUNICIPALITIES - Obradovic, Dragan Đura; Ranisavljević, Duško; Petrović, Zdravko (Economics of Agriculture, 2018)
There are numerous and diverse Serbian road users or traffic participants on a daily basis. Farm vehicles are also considered participants. In fact, from all the farm vehicles engaged in traffic, it is tractors that are involved the most in traffic accidents. In this paper, we will present valid data on tractor-related traffic accidents during the 2012-2016 period, with a focus on areas under the jurisdiction of two police administrations from different parts of Serbia - Valjevo and Subotica. By analyzing data on farmsteads and comparing traffic accidents in these areas, we pointed out the multiple negative economic effects and possible measures for their mitigating, as well as the differences between the regions of western and northern Serbia. This data, indicates that there should be more focus on the consequences resulting from these incidents as they indicate the most diverse segments of damage in the area of agriculture.